Effectiveness of Rational Emotive Behavior Therapy on Oppositional Defiant Disorder and Sexual Deviance in Working Children - Nezami, Shohreh (Psychological Research in Individuals with Exceptional Needs, 2026)
The present study aimed to investigate the effectiveness of Rational Emotive Behavior Therapy (REBT) on reducing oppositional defiant disorder and sexual deviance among working children in Tehran. This study employed a quasi-experimental design with pretest-posttest and control group. The statistical population consisted of male working children aged 9 to 11 years enrolled at Parto School affiliated with the Mehrafarin Charity Organization in Tehran during the 2025 academic year. Thirty participants were selected using convenience sampling and randomly assigned into experimental (n=15) and control (n=15) groups. The experimental group participated in eight 90-minute sessions of Rational Emotive Behavior Therapy conducted over four weeks, while the control group received no intervention. Data collection instruments included the Oppositional Defiant Disorder Questionnaire developed by Ahmadi (2013) and the Child Sexual Deviance Questionnaire developed by Rashidi (2013). Data were analyzed using analysis of covariance (ANCOVA) in SPSS version 26 after verifying statistical assumptions including normality, homogeneity of variances, and homogeneity of regression slopes. The results of ANCOVA demonstrated that Rational Emotive Behavior Therapy significantly reduced oppositional defiant disorder symptoms in the experimental group compared to the control group (F=295.73, p<0.001, η²=0.90). Furthermore, the intervention significantly decreased sexual deviance behaviors among participants in the experimental group (F=285.73, p<0.001, η²=0.90). The large effect sizes indicated that a substantial proportion of the variance in posttest scores was attributable to the REBT intervention. These findings confirmed both research hypotheses and demonstrated the strong effectiveness of REBT in improving disruptive and maladaptive behaviors among working children. The findings suggest that Rational Emotive Behavior Therapy is an effective and practical intervention for reducing oppositional defiant disorder and sexual deviance among working children. By helping children identify and modify irrational beliefs, improve emotional regulation, and develop adaptive coping strategies, REBT can significantly improve psychological and behavioral functioning in this vulnerable population.